PHILOSOPHIES UNDER MARXISM AND FEMINISM LITERARY THEORIES - Alem, Dawit Dibekulu; Guadu, Ayenew (Universitas Muhammadiyah Lampung, 2023)
Karl Marx and Friedrich Engels developed a corpus of ideas known as Marxism or socialism. The postulates of the Marxist school of thought offer the theoretical framework for the working class's struggles to realize socialism as a superior form of human society. The abolitionist movement of the late 1830s can be linked to the history of feminist ideology. Elizabeth Cady and Lucretia Mott spearheaded the Seneca Falls human rights convention, which served as the. Most recent breakthroughs in feminist thought and practice continue to be disregarded by both Marxist theory and practice. The production of people under patriarchal relations is examined, and feminist theory focuses on the conflicts that arise between women and men as a result of their different relationships to these two types of production. This definition of production, which is frequently used in much Marxist literature, is challenged by feminist theory. Because women in their households typically deal with patriarchy as individuals, feminist practice places a strong emphasis on developing consensus tactics, supporting women in their particular challenges, and assisting each woman in feeling both her oppression and her strength. The left largely misunderstands the importance of this tactic. While feminist activism is just as revolutionary as class struggle, its goal is different: it seeks to overthrow patriarchy. A large portion of the left's hostility toward feminism appears to be the result of misinterpreting Mao's idea of